Labyrinth und Turmbau zu Babel. Räumliches Erzählen bei Friedrich Dürrenmatt und Franz Kafka - Famula, Marta (Internationale germanistische und translatologische Tagung Presov 2008)

Numerical and Experimental Analysis of TEHD Lubrication of ZK Type Worm Gear Drives - Magyar, Balázs; Horák, P (VDI-Berichte 2108)

Investigation of the Lubrication of ZI Type Worm Gear Drives - Magyar, Balázs; Horák, P

Experimentelle Untersuchung der Zahnreibungszahl von Schneckengetrieben mit der Flankenform K - Magyar, Balázs; Horák, P; Sauer, B; Fábián, Cs (GÉP)

Distress in response to infidelities committed by the partners of close others: Siblings versus friends. - Bohner, Gerd; Echterhoff, Gerald; Glaß, Christian; Patrzek, Justine; Lampridis, Efthymios (Social psychology)

Novel drug delivery systems: Chitosan conjugates covalently attached to steroids with potential anticancer and agrochemical activity - Pérez Quiñones, Javier; Szopko, Richard; Schmidt, Claudia; Peniche Covas, Carlos (Carbohydrate Polymers)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Übergang Förderschule-Beruf – Förderschwerpunkt geistige Entwicklung - Heger, M.; Laubenstein, Désirée (In: Vierteljahresschrift für Heilpädagogik und ihre Nachbargebiete, 79. Jahrgang, Nr. 3,)

Arbeiten auf dem allgemeinen Arbeitsmarkt für Menschen mit geistiger Behinderung durch „Übergang Schule-Beruf“ - Laubenstein, Désirée; Heger, M. (In: Teilhabe, 49. Jahrgang, Nr. 3)

Integration auf den allgemeinen Arbeitsmarkt bei geistiger Behinderung: Utopie oder Perspektive - Laubenstein, Désirée; Heger, M. (In: Lernen konkret, 29. Jahrgang, Nr. 2)

Vorbereitung auf den Orthografieerwerb: Zur Berücksichtigung der Schrift in der vorschulischen Sprachförderung von Kindern mit Deutsch als Zweitsprache - Tophinke, Doris (Erwerb schriftsprachlicher Kompetenzen im DaZ-Kontext: Diagnose und Förderung)

Sooo schön. Andersschreiben untersuchen - Tophinke, Doris (Praxis Deutsch)

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt

Securitization and systematic risk in European banking: Empirical evidence - Uhde, André; Michalak, Tobias C. (Journal of Banking & Finance)
Using a unique dataset of 592 cash and synthetic securitizations issued by 54 banks from the EU-15 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a positive impact on the increase of European banks’ systematic risk. Baseline results hold when comparing estimated beta coefficients with a control group of similar non-securitizing banks. Building several sub-samples we additionally find that (a) the increase in systematic risk is more relevant for larger banks that repeatedly engage in securitization, (b) securitization is more important for small and medium financial institutions, (c) banks have a higher incentive to retain the larger part of credit risk as a quality signal at the beginning of the securitization business in Europe, and (d) the overall risk-shifting effect due to securitization is more distinct when the pre-event systematic risk is low.
Keywords: Credit risk transfer; Securitization; Systematic risk; Event study

Self-assembled quantum dots in a liquid-crystal-tunable microdisk resonator - Piegdon, Karoline A.; Offer, Matthias; Lorke, Axel; Urbanski, Martin; Hoischen, Andreas; Kitzerow, Heinz-Siegfried; Declair, Stefan; Förstner, Jens; Meier, Torsten; Reuter, Dirk; Wieck, Andreas D.; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)

On Scarcity and Abundance. Three Types of Social Reasoning in More’s, Campanellas and Bacon’s Utopian Drafts - Hagengruber, Ruth Edith (Utopia. La Busqueda de la Sociedad ideal)

Ulrich Steinvorth. Rethinking the Western Understanding of the Self (Cambridge u.a.: Cambridge UP, 2009) - Hagengruber, Ruth Edith (Notre Dame Philosophical Reviews)

Überschuldung - Bildungsbezogene Perspektive - Schlegel-Matthies, Kirsten (Auf dem Weg zum Jugendintegrationskonzept. Grundlagen und Herausforderungen angesichts veränderter Lebenslagen junger Menschen)

Arbitration and Peacemaking - Kamp, Hermann (Medieval Warfare and Military Technology)

New Masters and Old Rituals. Edward I, Robert the Bruce, Philipp the Fair and the Role of Rituals with Conquest - Kamp, Hermann (State, Power and Violence)

Die Macht der Spielregeln im Mittelalter. Eine Einführung - Kamp, Hermann (Die Spielregeln der Mächtigen. Mittelalterliche Politik zwischen Gewohnheiten und Konventionen)

Die Spielregeln der Mächtigen. Mittelalterliche Politik zwischen Gewohnheiten und Konventionen

Von Diana zu Minerva: Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts - Hagengruber, Ruth Edith (Von Diana zu Minerva. Philosophierende Aristokratinnen des 17. und 18. Jahrhunderts)

Making Worlds. Epistemological, Ontological and Political Dimensions of Technoscience - Weber, Jutta (Poiesis and Praxis. International Journal of Ethics of Science and Technology Assessment 1/2010)

‘Security’ Architectures, New Ontologies and the Category of Gender. Contemporary Challenges in Feminist Technoscience Studies - Weber, Jutta (GenderChange in Academia. Re-mapping the Fields of Work, Knowledge, and Politics from a Gender Perspective)

Neue Roboterträume. Über Wunsch und Wirklichkeit der Dienstleistungsrobotik - Weber, Jutta (Roboterträume)

New Robot Dreams. On Desire and Reality in Service Robotics - Weber, Jutta (Roboterträume)

Armchair Warfare ‘on Terrorism’. On Robots, Targeted Assassinations and Strategic Violations of International Law - Weber, Jutta (Thinking Machines and the Philosophy of Computer Science: Concepts and Principles)

Gender, Diversity and a Competence Based Computer Science Curriculum - Weber, Jutta; Crutzen, Cecile (Festschrift for Christina Mörtberg)

Situiertheit, Verkörperung, Gefühl: Unscharfe Begriffe als technowissenschaftliche Innovationsressource - Weber, Jutta (Geschlecht und Innovation. Gender-Mainstreaming im Techno-Wissenschaftsbetrieb. Teilband 4. Internationale Frauen- und Geschlechterforschung in Niedersachsen)

Flexibel, situiert & unberechenbar. Über Mensch und Maschine im Zeitalter der Technoscience - Weber, Jutta (Der Wert des menschlichen Lebens im 21. Jahrhundert. Zu den Grenzen der menschlichen Verfügungsmacht. 13. Internationale Europakonferenz)

Closing the Gap between UML-based Modeling and Simulation of Combined HW/SW Systems - Mischkalla, Fabian; He, Da; Müller, Wolfgang (Proceedings of DATE’10)
UML is widely applied for the specification and modeling of software and some studies have demonstrated that it is applicable for HW/SW codesign. However, in this area there is still a big gap from UML modeling to SystemC-based verification and synthesis environments. This paper presents an efficient approach to bridge this gap in the context of Systems-on-a-Chip (SoC) design. We propose a framework for the seamless integration of a customized SysML entry with code generation for HW/SW cosimulation and high-level FPGA synthesis. For this, we extended the SysML UML profile by SystemC and synthesis capabilities. Two case studies demonstrate the applicability of our approach.
Keywords: Unified modeling language; Field programmable gate arrays; Bridges; Helium; Real time systems; Operating systems; Documentation; Application software; XML; Space exploration

Assertion-Based Verification of RTOS Properties - Oliveira, Marcio F. S.; Zabel, Henning; Müller, Wolfgang (Proceedings of DATE’10)
Today, mobile and embedded real time systems have to cope with the migration and allocation of multiple software tasks running on top of a real time operating system (RTOS) residing on one or several processors. For scaling of each task set and processor configuration, instruction set simulation and worst case timing analysis are typically applied. This paper presents a complementary approach for the verification of RTOS properties based on an abstract RTOS-Model in SystemC. We apply IEEE P1850 PSL for which we present an approach and first experiences for the assertion-based verification of RTOS properties.
Keywords: Operating systems; Real time systems; Timing; Hardware; Analytical models; Embedded software; Software systems; Processor scheduling; Software performance; Performance analysis

Timing Modeling and Analysis for AUTOSAR-Based Software Development - A Case Study - Klobedanz, Kay; Kuznik, Christoph; Thuy, Andre; Müller, Wolfgang (Proceedings of DATE’10, Dresden)
Safety-critical automotive systems must fulfill hard real-time constraints for reliability and safety. This paper presents a case study for the application of an AUTOSAR-based language for timing modeling and analysis. We present and apply the Timing Augmented Description Language (TADL) and demonstrate a methodology for the development of a speed-adaptive steer-by-wire system. We examine the impact of TADL and the methodology on the development process and the suitability and interoperability of the applied tools with respect to the AUTOSAR-based tool chain in the context of our case study.
Keywords: Timing; Programming; Automotive engineering; Application software; Hardware; Computer architecture; Communication system software; Software architecture; Delay; Software standards

A Systematic Approach to Combined HW/SW System Test - Krupp, Alexander; Müller, Wolfgang (Proceedings of DATE’10)
Today we can identify a big gap between requirement specification and the generation of test environments. This article extends the Classification Tree Method for Embedded Systems (CTM/ES) to fill this gap by new concepts for the precise specification of stimuli for operational ranges of continuous control systems. It introduces novel means for continuous acceptance criteria definition and for functional coverage definition.
Keywords: System testing; Automatic testing; Object oriented modeling; Classification tree analysis; Automotive engineering; Mathematical model; Embedded system; Control systems; Electronic equipment testing; Software testing

RTOS-Aware Refinement for TLM2.0-based HW/SW Design - Becker, Markus; Di Guglielmo, Giuseppe; Fummi, Franco; Müller, Wolfgang; Pravadelli, Graziano; Xie, Tao (Proceedings of DATE’10)
Refinement of untimed TLM models into a timed HW/SW platform is a step by step design process which is a trade-off between timing accuracy of the used models and correct estimation of the final timing performance. The use of an RTOS on the target platform is mandatory in the case real-time properties must be guaranteed. Thus, the question is when the RTOS must be introduced in this step by step refinement process. This paper proposes a four-level RTOS-aware refinement methodology that, starting from an untimed TLM SystemC description of the whole system, progressively introduce HW/SW partitioning, timing, device driver and RTOS functionalities, till to obtain an accurate model of the final platform, where SW tasks run upon an RTOS hosted by QEMU and HW components are modeled by cycle accurate TLM descriptions. Each refinement level allows the designer to estimate more and more accurate timing properties, thus anticipating design decisions without being constrained to leave timing analysis to the final step of the refinement. The effectiveness of the methodology has been evaluated in the design of two complex platforms.
Keywords: Timing; Hardware; Operating systems; Process design; Accuracy; Standards development; Context modeling; Real time systems; Communication channels; Microprogramming

A Mixed Level Simulation Environment for Stepwise RTOS Software Refinement - Becker, Markus; Zabel, Henning; Müller, Wolfgang
In this article, we present a flexible simulation environment for embedded real-time software refinement by a mixed level cosimulation. For this, we combine the native speed of an abstract real-time operating system (RTOS) model in SystemC with dynamic binary translation for fast Instruction Set Simulation (ISS) by QEMU. In order to support stepwise RTOS software refinement from system level to the target software, each task can be separately migrated between the native execution and the ISS. By adapting the dynamic binary translation approach to an efficient but yet very accurate synchronization scheme the overhead of QEMU user mode execution is only factor two compared to native SystemC. Furthermore, the simulation speed increases almost linearly according to the utilization of the task set abstracted by the native execution. Hereby, the simulation time can be considerably reduced by cosimulating just a subset of tasks on QEMU.
Keywords: Application Programming Interface User Mode Kernel Space System Level Design Mixed Level

Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Zabel, Henning; Müller, Wolfgang; Zhi, Yuan
In this paper we present new concepts to resolve ECU (Electronic Control Unit) failures in FlexRay networks. Our approach extends the FlexRay bus schedule by redundant slots with modifications in the communication and slot assignment. We introduce additional backup nodes to replace faulty nodes. To reduce the required memory resources of the backup nodes, we distribute redundant tasks over different nodes and propose the migration of tasks to the backup node at runtime. We investigate different solutions to migrate the redundant tasks to the backup node by time-triggered and event-triggered transmissions.
Keywords: Faulty Node Static Segment Slot Assignment Task Migration Communication Controller

A UML Profile for SysML-Based Comodeling for Embedded Systems Simulation and Synthesis - Mischkalla, Fabian; Müller, Wolfgang; He, Da (Proceedings of the M-BED Workshop)
It's wide application in the area of software engineering, UML is still not fully accepted for other engineering domains like for electronic systems design. The main obstacle is due to a major gap in the design flow between UML-based modeling and verification. To overcome this gap, we introduce a UML profile for synthesizable SystemC and C and present its implementation in the context of the advanced SysML modeling environment of ARTiSAN Studio. We demonstrate how to customize Studio for SystemC/C comodeling so that it can serve as a verification and synthesis front-end.

Eine strukturierte Methode zur Generierung von SystemVerilog-Testumgebungen aus textuellen Anforderungsbeschreibungen - Bol, Alexander; Müller, Wolfgang; Krupp, Alexander (Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV))

The SATURN Approach to SysML-based HW/SW Codesign - Müller, Wolfgang; He, Da; Mischkalla, Fabian; Wegele, Arthur; Larkham, Adrian; Whiston, Paul; Penil, Pablo; Villar, Eugenio; Mitas, Nikolaos; Kritharidis, Dimitros; Azcarate, Florent; Carballeda, Manuel (Proceedings of the IEEE Computer Society Annual Symposium on VLSI)
The main obstacle for the wide acceptance of UML and SysML in the design of electronic systems is due to a major gap in the design flow between UML-based modeling and SystemC-based verification. To overcome this gap, we present an approach developed in the SATURN project which introduces UML profiles for the co-modeling of SystemC and C with code generation support in the context of the SysML tool suite ARTiSAN Studio®. We finally discuss the evaluation of the approach by two case studies.
Keywords: Communicate Sequential Process Virtual Platform Smart Camera Synchronous Data Flow Artisan Studio

Generation of Executable Testbenches from Natural Language Requirement Specifications for Embedded Real-Time Systems - Müller, Wolfgang; Bol, Alexander; Krupp, Alexander; Lundkvist, Ola
We introduce a structured methodology for the generation of executable test environments from textual requirement specifications via UML class diagrams and the application of the classification tree methodology for embedded systems. The first phase is a stepwise transformation from unstructured English text into a textual normal form (TNF), which is automatically translated into UML class diagrams. After annotations of the class diagrams and the definition of test cases by sequence diagrams, both are converted into classification trees. From the classification trees we can finally generate SystemVerilog code. The methodology is introduced and evaluated by the example of an Adaptive Cruise Controller.
Keywords: Natural Language UML SystemVerilog Testbenches

Mutation-Analysis Directed Constrained Random Verification - Xie, Tao; Letombe, Florian; Müller, Wolfgang

An Eclipse-based Framework for the IP-XACT-enabled Assembly of Mixed-Level IPs - Xie, Tao; Defo, Gilles B.; Müller, Wolfgang

Verification of a CAN Bus Model in SystemC with Functional Coverage - Defo, Gilles B.; Müller, Wolfgang; Kuznik, Christoph (Proceedings of SIES 2010)
Many heterogeneous embedded systems, for example industrial automation and automotive applications, require hard-real time constraints to be exhaustively verified - which is a challenging task for the verification engineer. To cope with complexity, verification techniques working on different abstraction levels are best practice. SystemC is a versatile C++ based design and verification language, offering various mechanisms and constructs required for embedded systems modeling. Using the add-on SystemC Verification Library (SCV) elemental constrained-random stimuli techniques may be used for verification. However, SCV has several drawbacks such as lack of functional coverage. In this paper we present a functional coverage library that implements parts of the IEEE 1800-2005 SystemVerilog standard and allows capturing functional coverage throughout the design and verification process with SystemC. Moreover, we will demonstrate the usability of the approach with a case study working on a CAN bus model written in SystemC.
Keywords: Libraries; Generators; Transfer functions; Monitoring; Computational modeling; Driver circuits; Adaptation model

Distributed Coordination of Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Müller, Wolfgang; Kerstan, Timo (Proceedings of SIES 2010)
In this paper we present an approach to increase the fault tolerance in FlexRay networks by introducing backup nodes to replace defect ECUs (Electronic Control Units). In order to reduce the memory requirements of such backup nodes, we distribute redundant tasks over different nodes and propose the distributed coordinated migration of tasks of the defect ECU to the backup node at runtime. This approach enhances our former work in, where we extended the FlexRay bus schedule by redundant slots to consider changes in the communication/slot assignment and investigated and evaluated different solutions to migrate the redundant tasks to the backup node using the static and/or dynamic segment of the communication cycle for transmissions. We present the approach of distributed coordination for migration and communication instead of additional dedicated coordinator nodes to further increase the fault tolerance. With this approach we improve the safety of FlexRay networks by avoiding a possible single point of failure due to a dedicated coordinator node also minimizing the necessary time needed for a reconfiguration after an ECU failure. Furthermore, we reduce the overhead within the communication and the demand for additional hardware components.
Keywords: Fault tolerant systems; Protocols; Redundancy; Runtime; Payloads; Schedules

Verification of Real-Time Properties for Hardware-Dependant Software - Müller, Wolfgang; da S. Oliveira, Marcio F.; Zabel, Henning; Becker, Markus (Proceedings of HLDVT2010)
Seamless HW/SW codesign flows support early verification of hardware and Hardware-dependent Software (HdS) like drivers, operating systems, and firmware. For early estimation and verification, the application of SystemC in combination with Instruction Set Simulators and Software Emulators like QEMU is widely accepted. In this article, we present an advanced design flow for HW, (RT)OS and HdS refinement and verification with focus on the transition from abstract RTOS verification to full system RTOS/HdS emulation. In the context of assertion-based verification, we introduce a set of generic real-time properties which can be reused and verified at different abstraction levels and discuss their application. The properties are presented by the means of IEEE standard PSL assertions which are applied for mixed SystemC/HdS models.
Keywords: Hardware; Microprogramming; Application software; Timing; Protocols; Virtual prototyping; Real time systems; Sampling methods; Operating systems; Emulation

Design Space Abstraction and Metamodeling for Embedded Systems Design Space Exploration - Oliveira, Marcio F. S.; do Nascimento, Francisco Assis M.; Müller, Wolfgang (Proceedings of MoMPES 2010)

Evidenzbasierte Soziale Arbeit. Zur Rolle wissenschaftlichen Wissens für sozialarbeiterisches Handeln - Dahmen, Stephan